2023
DOI: 10.3390/ijms241512015
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Efficacy of Saccharomyces boulardii in Metabolic Syndrome Treatment: A Narrative Review of What Is Known So Far

Abstract: Metabolic syndrome (MetS) is characterized by complex metabolic changes involving a cluster of co-occurring conditions, such as abdominal obesity, high blood pressure, high fasting plasma glucose, high serum triglycerides, and high LDL cholesterol levels or low HDL cholesterol levels. The incidence and risk factors of MetS occurrence increase every year. It is estimated that MetS affects approximately 30% of the population of some countries. Therefore, novel strategies are being studied to reduce the negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 111 publications
1
2
0
Order By: Relevance
“…55 The ability of S. boulardii to alter the lipid profile in the plasma and liver is directly related to the absorption of cholesterol by the yeast cell wall or indirectly related to the modulation of the gastrointestinal microbiota. 57 The S. boulardii dose used in the current study showed a positive effect on intestinal health in previously conducted studies. 58 In our study, TC and LDL cholesterol did not change significantly after 12-week administration of probiotics and octacosanol.…”
Section: Discussionsupporting
confidence: 51%
“…55 The ability of S. boulardii to alter the lipid profile in the plasma and liver is directly related to the absorption of cholesterol by the yeast cell wall or indirectly related to the modulation of the gastrointestinal microbiota. 57 The S. boulardii dose used in the current study showed a positive effect on intestinal health in previously conducted studies. 58 In our study, TC and LDL cholesterol did not change significantly after 12-week administration of probiotics and octacosanol.…”
Section: Discussionsupporting
confidence: 51%
“…Traditional pharmacological treatments are often associated with side effects and limitations, necessitating the exploration of alternative solutions. In this context, probiotics have emerged as an innovative approach to managing metabolic disorders [11].…”
Section: Introductionmentioning
confidence: 99%
“…uncontrolled hyperthyroidism or hypothyroidism;(11) clinically significant hematological, cardiac, lung, or neurological disease or other serious systemic disorders;(12) clinically significant renal dysfunction or chronic renal failure; (13) clinically significant…”
mentioning
confidence: 99%